2012
DOI: 10.1007/s10695-012-9650-0
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in haematological and biochemical parameters of Catla catla exposed to sub-lethal concentration of cypermethrin

Abstract: A 60-day experiment was carried out to study the effect of sub-lethal concentration of cypermethrin (1/10th of LC(50)) exposure on haematological and biochemical parameters of the Indian major carp, Catla catla fingerlings. Under exposure, the total erythrocyte count, total leucocyte count, haemoglobin content and haematocrit were decreased. All the studied serum parameters viz. total serum protein, albumin, globulin contents and albumin-globulin ratio were significantly decreased in cypermethrin-exposed fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 34 publications
(17 reference statements)
3
26
0
Order By: Relevance
“…Gluconeogenesis is promoted by the incorporation of keto acids into tricarboxylic acid (TCA) cycle via active transdeamination (Neelima et al 2013). Studies on cypermethrin-induced increase in the activities of hepatic AST and ALT in C. batrachus (Begum 2005), Cirrhinus mrigala (Prasanth and Neelagund 2008), Channa punctatus and C. batrachus (Kumar et al 2011), L. rohita (Tiwari et al 2012), Catla catla (Vani et al 2012) and Prochilodus lineatus (Loteste et al 2013) indicate that fish utilize amino acids to overcome the stress of cypermethrin. Changes in glucose metabolism were also linked with the activities of hepatic alkaline phosphatase, which were decreased in cypermethrin-treated O. niloticus as compared to control.…”
Section: Biochemical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Gluconeogenesis is promoted by the incorporation of keto acids into tricarboxylic acid (TCA) cycle via active transdeamination (Neelima et al 2013). Studies on cypermethrin-induced increase in the activities of hepatic AST and ALT in C. batrachus (Begum 2005), Cirrhinus mrigala (Prasanth and Neelagund 2008), Channa punctatus and C. batrachus (Kumar et al 2011), L. rohita (Tiwari et al 2012), Catla catla (Vani et al 2012) and Prochilodus lineatus (Loteste et al 2013) indicate that fish utilize amino acids to overcome the stress of cypermethrin. Changes in glucose metabolism were also linked with the activities of hepatic alkaline phosphatase, which were decreased in cypermethrin-treated O. niloticus as compared to control.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…This was due to poor efficiency in feed conversion, net protein utilization and subsequent poor deposition of protein and lipid in the muscle. There are evidence that cypermethrin can reduce the protein level of serum (Vani et al 2012;Kannan et al 2014), gills and liver (Begum 2005), muscle and kidneys (Begum 2007) in several species of fish. Gijare et al (2011) also found that the lipid content was decreased in O. punctatus due to cypermethrin treatment.…”
Section: Effects On Growth and Biochemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common blood parameters monitored include total erythrocyte count, total leucocyte count, and haemoglobin and haematocrit content, which were found to decrease on cypermethrin exposure in the Indian major carps Labeo rohita and Catla catla [7]. However, several workers [811] recorded increased lymphocyte, leucocyte, and erythrocyte counts, packed cell volume, and hemoglobin in several species of fishes challenged with cypermethrin, deltamethrin, and fenvalerate.…”
Section: Hematological Biomarkersmentioning
confidence: 99%
“…Jayaprakash and Shettu [12] observed a decrease in hemoglobin content, total erythrocyte count, packed cell volume, mean corpuscular volume, and mean corpuscular hemoglobin concentration and an increase in total leukocyte count, mean corpuscular volume, erythrocyte sedimentation rate, and clotting time values in the snakehead, Channa punctatus, exposed to deltamethrin. Other hematological variables such as total serum protein, albumin, and globulin contents, albumin-globulin ratio, plasma glucose, alanine aminotransferase, and cholinesterase were reduced in fishes exposed to cypermethrin and deltamethrin [7, 13]. On the contrary, significantly higher erythrocyte count, haemoglobin, haematocrit, plasma total protein, albumins, calcium, and ammonia contents, and activities of aspartate aminotransferase and creatine kinase were observed in the deltamethrin-treated group compared to the control group [13].…”
Section: Hematological Biomarkersmentioning
confidence: 99%